Efektivitas Katalis Heterogen Fly Ash (FA-SO3H) pada Sintesis Biodiesel dari Palm Fatty Acid Distillate - Sudrajat Harris Abdulloh; Eko Andrijanto; Saripudin Saripudin; Anindya Indrita Putri; Dhea Nurul; Lidya Elizabeth (Fluida, 2024)
The increase in fuel use along with the decline in production of petroleum exploration activities encourages efforts to find alternative fuels, one of which is biodiesel from PFAD (Palm Fatty Acid Distillate) with production reaching 6,000,000 tons while its utilization is still low. Biodiesel production from PFAD using Fly ash (FA)-SO3H catalyst which is a heterogeneous catalyst through esterification method. FA used in this study was wet impregnated using 6M sulfuric acid (H2SO4) for 24 hours, so that the highest acid concentration was obtained at a calcination temperature of 500 â°C of 1.1654 mmol/gram. The research was conducted with Response Surface Method (RSM) with Box Behnken Design model in Design Expert 13 software and 13 runs were obtained. The resulting model from RSM was obtained as optimum conditions at catalyst loading (%-w) 5-10, methanol:PFAD molar ratio (n/n) 10:1-30:1, reaction time 3-5 hours and temperature 60 â°C. Based on the experimental results and ANOVA, the high conversion is influenced by the high catalyst loading and methanol:PFAD ratio (n/n), with the conversion obtained of 72.89% at catalyst loading of 10%-w, methanol:PFAD molar ratio of 20 (n/n) and time for 5 hours.